Composites: An Amorphous Red Phosphorus/Carbon Composite as a Promising Anode Material for Sodium Ion Batteries (Adv. Mater. 22/2013). (10th June 2013) - Kim, Youngjin; Park, Yuwon; Choi, Aram; Choi, Nam‐Soon; Kim, Jeongsoo; Lee, Junesoo; Ryu, Ji Heon; Oh, Seung M.; Lee, Kyu Tae
<x xml:space="preserve">Abstract</x> Na‐ion batteries now face the critical problem of lower energy density than Li‐ion batteries, although they have gained recognition as promising next‐generation batteries to replace Li‐ion batteries. An amorphous red phosphorus/carbon composite anode material is for the first time examined as a solution to improve energy density, and shows remarkable electrochemical performance including high reversible capacity of 1890 mA h g−1. Further details can be found in the article by Kyu Tae Lee, Seung M. Oh, and co‐workers on page 3045. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>